High-Frequency Monitoring of Households : Summary of Results from Survey Round 1, 01-07 May 2020 - Purnamasari, Ririn; Ali, Rabia (World Bank, Washington, DC, 2020)
This brief presents findings from the first of five rounds of a nationally representative panel survey of 4,338 households across 40 districts and 35 cities in 27 provinces of Indonesia. The survey was implemented through 15 to 20-minute phone interviews. To achieve the program targets Government of Indonesia (GOI) has committed to, implementation efforts need to focus much more sharply on improving delivery of assistance to targeted poor and vulnerable households and ensure that those engaged in hard-hit non-farm businesses benefit either from expansion of existing social assistance or new economic relief programs.